CFD Study of Gas-liquid Hydrodynamics in a Bubble Column - Mohd Shahimie, Selamat; Jolius, Gimbun (Penerbit UMP, 2011)
This paper presents a computational fluid dynamics (CFD) of the gas-liquid flow in a bubble column. Multiphase simulations were performed using an Eulerian-Eulerian two-fluid model besides considering the drag coefficient model suitable for spherical and distorted bubbles. The interfacial force modelling also considered the effect of the void fractions on the drag coefficient. The CFD predictions were compared to the experimental measurement adopted from literature. The CFD predicts the turbulent kinetic energy, gas hold-up and the liquid axial velocity fairly well, although the results seem to suggest that further improvement to both the interfacial force model and two-fluid modeling approaches is necessary. It is clear from the modeling exercise performed in this work that CFD is a promising method for modeling the performance of bubble column. Furthermore, the CFD method is certainly less expensive than the experimental characterization studies.